The Influence of Work Commitment Towards Employee Performance in Pastry & Bakery Department at Four Seasons Resorts Bali - Ena Vania Edgina Sembiring; Mega Hernawati Harefa; Devia Febrina (Brilliant International Journal Of Management And Tourism, 2024)
This study aims to determine the influence of work commitment on employee performance in the Pastry and Bakery Department at Four Seasons Hotel and Resorts Jimbaran, Bali. Work commitment is considered an important factor in improving employee performance because committed employees tend to be more engaged, responsible, and motivated in carrying out their duties. This research employed a descriptive and causal quantitative approach. The population consisted of 45 employees working in the Pastry and Bakery Department, and census sampling was used so that all employees became respondents. Data were collected through questionnaires, interviews, and observations. The data were analyzed using validity and reliability tests, descriptive statistics, normality test, correlation analysis, coefficient of determination, simple linear regression, and hypothesis testing using the Z-test. The findings revealed that work commitment has a significant influence on employee performance. The correlation coefficient was 0.819, indicating a strong positive relationship between work commitment and employee performance. The coefficient of determination showed that 67.10% of employee performance could be explained by work commitment, while the remaining 32.90% was influenced by other factors outside the research model. Furthermore, the Z-test result showed that Zcount was greater than Ztable (5.43 > 1.96), indicating that the alternative hypothesis was accepted. Therefore, work commitment significantly influences employee performance at Four Seasons Hotel and Resorts Jimbaran, Bali